DIU ABDOMINOPÉLVICO: MANEJO LAPAROSCÓPICO - Jaime Zarhi T; Fernando Vacca G; Johnny Jarsún J; J. Pablo Sepúlveda V; Luis Zapata P (Permanyer, 2005)
Se presenta la experiencia de 18 pacientes sometidas a cirugía laparoscópica por DIU intraabdominal, en las cuales el diagnóstico se realizó por ecotomografía transvaginal y radiografía de pelvis. En todos los casos su extracción se realizó sin complicaciones ni conversión a laparotomía. Se discute el cuadro clínico, diagnóstico, tratamiento y eventuales complicaciones Eighteen patients with intra-abdominal DIU whose diagnosis was done by transvaginal ecotomography and pelvic x-ray and in whom the device was drawn by laparoscopic surgery are presented in this study. There was successful procedure in all cases without immediate or ulterior complications and none of them needed conversion to laparotomy. The clinical picture, diagnosis, treatment and eventual complications are discussed